(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Acid erosion and chemical whitening agents cause significant damage to dental enamel. The main consequences include mineral loss, increased porosity, and heightened sensitivity. This article analyzes the causes of acid erosion, the effects of bleaching agents, and modern preventive strategies.